2007
DOI: 10.1016/j.bbi.2006.10.012
|View full text |Cite
|
Sign up to set email alerts
|

Intrathecal interleukin-10 gene therapy attenuates paclitaxel-induced mechanical allodynia and proinflammatory cytokine expression in dorsal root ganglia in rats

Abstract: Paclitaxel is a commonly used cancer chemotherapy drug that frequently causes painful peripheral neuropathies. The mechanisms underlying this dose-limiting side effect are poorly understood. Growing evidence supports that proinflammatory cytokines, such as interleukin-1 (IL-1) and tumor necrosis factor (TNF), released by activated spinal glial cells and within the dorsal root ganglia (DRG) are critical in enhancing pain in various animal models of neuropathic pain. Whether these cytokines are involved in pacli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
228
3
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 274 publications
(247 citation statements)
references
References 61 publications
12
228
3
2
Order By: Relevance
“…Nitric oxide was found to be key in mediating elevations of IL1, TNF and IL6 mRNA and protein in lumbar spinal cord leading to allodynia in gp120-treated animals (Holguin et al, 2004). In addition, IL-1 was shown to be important for the maintenance of neuropathic pain states because established neuropathic pain can be reversed either by proinflammatory cytokine antagonists or by the anti-inflammatory cytokine interleukin-10 (IL10) (Abraham et al, 2004, Johnston et al, 2004, Ledeboer et al, 2007, Milligan et al, 2005a, Milligan et al, 2005b, Milligan et al, 2006a, Milligan et al, 2006b, Plunkett et al, 2001, Sloane et al, submitted, Yu et al, 2003 that inhibits the production and activity of proinflammatory cytokines ). Such results are important when one is considering the potential of targeting proinflammatory cytokines for clinical pain control.…”
Section: Pathological Pain Statesmentioning
confidence: 99%
See 2 more Smart Citations
“…Nitric oxide was found to be key in mediating elevations of IL1, TNF and IL6 mRNA and protein in lumbar spinal cord leading to allodynia in gp120-treated animals (Holguin et al, 2004). In addition, IL-1 was shown to be important for the maintenance of neuropathic pain states because established neuropathic pain can be reversed either by proinflammatory cytokine antagonists or by the anti-inflammatory cytokine interleukin-10 (IL10) (Abraham et al, 2004, Johnston et al, 2004, Ledeboer et al, 2007, Milligan et al, 2005a, Milligan et al, 2005b, Milligan et al, 2006a, Milligan et al, 2006b, Plunkett et al, 2001, Sloane et al, submitted, Yu et al, 2003 that inhibits the production and activity of proinflammatory cytokines ). Such results are important when one is considering the potential of targeting proinflammatory cytokines for clinical pain control.…”
Section: Pathological Pain Statesmentioning
confidence: 99%
“…Gene-encoding vectors, such as viral and non-viral vectors to deliver the IL-2, IL-4 or IL-10 gene to the spinal cord to control pain in neuropathic rodent models have been examined and show promise (Hao et al, 2006, Ledeboer et al, 2007, Milligan et al, 2005a, Milligan et al, 2005b, Yao et al, 2003, Yao et al, 2002a, Yao et al, 2002b. For example, spinal cord over-expression of IL-10 controls pain produced by sciatic inflammatory neuropathy and chronic constriction injury (Milligan et al, 2005a, Milligan et al, 2007, Milligan et al, 2005b. The duration of pain control by spinal IL-10 gene therapy was observed from 1-3 months (Milligan et al, 2006a, Sloane et al, submitted).…”
Section: Targeting Activated Glia With Anti-inflammatory Cytokines Tomentioning
confidence: 99%
See 1 more Smart Citation
“…intrathecal (i.t.) delivery is a commonly used method for chronic pain gene therapy (15)(16)(17)(18). hPPe delivered i.t.…”
Section: Introductionmentioning
confidence: 99%
“…LC cells may contribute to pain development by different mechanisms including release of nitric oxide (NO) [45], proinflammatory cytokines [46], and neurotrophic factors [47], that in turn cause spontaneous neuronal discharge, nociceptor sensitization, and mechano-hypersensitivity. It has also been demonstrated that paclitaxel-induced neuropathic pain is associated with TNF-and IL-1 induction in lumbar DRGs [48]. Glial cell inhibitors attenuate paclitaxel-and vincristine-induced neuropathic pain [49,50], supporting a role for activated glial cells in this condition.…”
Section: Introductionmentioning
confidence: 99%